PENTINGNYA KERJASAMA TIM DALAM MERAIH SUKSES USAHA (Universitas Wijayakusuma Purwokerto, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a big role in facing the global recession because MSMEs contribute greatly to Gross Domestic Product and employment. Yasinta Joint Business Group (KUB) which is located at Jl. Wijayakusuma RT 06 RW 08 Sokawera Village, Cilongok District, Banyumas Regency is a joint business group whose members are also MSME actors. With the many types of business carried out by KUB Yasinta, proper human resource management is needed to be truly effective in achieving organizational goals. It is very necessary to have cooperation between members so that work is not done individually but can be done by working together and collaborating to increase business productivity. This community service activity aims to increase KUB Yasinta members' understanding of the importance of teamwork, so that organizational goals can be achieved more effectively and efficiently. The result of service activities is that they understand the importance of teamwork. Each member can collaborate with other members to improve their performance, so that in the end it can improve the overall performance of the organization and its business can be expected to experience development in the long term in the future.